Scrutinizing EFL students' plagiarism practice - Muluk, Safrul; Yanis, Fani Rahma; Dahliana, Syarifah; Amiruddin, Amiruddin (Englisia: Journal of Language, Education, and Humanities, 2021)
The current study was designed to investigate the types of plagiarism that appear in EFL students’ theses at Ar-Raniry State Islamic University, Indonesia. It sought to examine the plagiarism level, and investigate the triggering factors encouraging these EFL students of the 2019 batch to plagiarize. This study used a qualitative method with a case study approach. The participants in this study were ten EFL students of the 2019 batch and their theses. The participants were randomly selected. The data collection was carried out using two research instruments, namely document analysis, and interview. The researcher analyzed the student's thesis using Plagiarism Checker X. The results of the document analysis showed that there were two types of plagiarism detected in the student's thesis, namely word for word and mosaic plagiarism. Second, the researcher found that the plagiarism level of the 2019 batch English students' thesis of UIN Ar-Raniry was at the low-level plagiarism category, which can be observed from the result of the similarity index. The level of plagiarism found in these theses was less than 30%, still at an acceptable level as stipulated by the university regulation. Meanwhile, the result of the interview showed that all participants know what plagiarism is and they think that plagiarism is a negative conduct. Several factors influences EFL English students to plagiarize, such as poor time management, laziness, poor paraphrasing skills, affordable internet access, and running out of ideas.